Earthquake scenario-specific framework for spatial accessibility analysis (SAA) of emergency shelters: a case study in Xichang City, Sichuan Province, China - Wang, Ziyue; Cheng, Jia; Xu, Chong (Frontiers in Earth Science, 2024)
The spatial accessibility of emergency shelters, indicating the difficulty of evacuation and rescue, is crucial for disaster mitigation and emergency management. To analyze accessibility, an effective approach is to evaluate the service capacity of emergency shelters. Multifaceted factors were employed to enhance the quantitative accuracy of accessibility indicators. However, scenario-specific analysis has not been emphasized. Considering the devastating potential of great earthquake disasters, we cannot ignore the impact of these scenarios on emergency shelter accessibility, especially in areas with high seismic risk. In this study, we developed an earthquake scenario-specific framework for spatial accessibility analysis (SAA), which integrates the service capacity of emergency shelters and the impact of strong ground motion and fault rupturing. We applied this framework to the urban area of Xichang City in Sichuan Province, western China. Xichang City, located in the linked area of the Anninghe fault and Zemuhe fault with many extreme historical earthquake disaster records, is prone to high seismic risk. We firstly collected emergency shelter and road network data in Xichang City. We then applied SAA based on the road network, using the network analysis method. After that, we analyzed the impact of strong ground motion on accessibility and generated the setback zone of fault rupturing. We integrated the effect of strong ground motion on accessibility within the setback zone of active faults. Finally, we generated a comprehensive accessibility map, considering both the predicted strong ground motion and potential fault rupturing. Our results show that the accessibility level changed in several towns of urban Xichang City due to strong ground motion and fault rupturing. The accessibility level decreased in Lizhou, Xingsheng, and Anning Towns. For areas with mapped fault lines, the accessibility level is Very-Low. Our results demonstrate the impact of earthquake damage on the accessibility of emergency shelters and the complexity of evacuation in earthquake scenarios. In general, we added earthquake rupturing and ground motion characteristics into the SAA framework. This framework will help us enhance the reliability of SAA and the feasibility of seismic vulnerability evaluation.